Language learning strategies among Vietnamese EFL High School students - Ngo Cong-Lem (Universitas Katolik Indonesia Atma Jaya, 2019)
Despite productive research on language learning strategies (LLS), LLS is still a multifaceted topic subject to controversy. Thus, previous researchers have encouraged conducting further LLS research in different educational contexts and student population. The current study was conducted to examine the LLS use among high school students, a relatively neglected population in previous LLS studies. Participants in the study were 83 Vietnamese tenth-graders who were administered the Strategy Inventory for Language Learning (SILL) by Oxford (1990), including six subscales: memory-related, cognitive, compensatory, metacognitive, affective and social strategies. The results suggested that high school learners utilized a wide range of language learning strategies at a medium level of frequency, indicating a necessity for more explicit LLS instruction. While metacognitive strategies were reported as the most frequently utilized strategies, affective strategies were the least. Cognitive strategies, which were strongly related to other LLS groups, tended to play the central role in the language learners’ LLS employment. Gender was confirmed to be a significant factor that influenced the students’ LLS usage only in the case of social strategies. Pedagogical implications regarding strategy instruction were discussed.